2016
DOI: 10.3390/bios6030035
|View full text |Cite
|
Sign up to set email alerts
|

MIPs and Aptamers for Recognition of Proteins in Biomimetic Sensing

Abstract: Biomimetic binders and catalysts have been generated in order to substitute the biological pendants in separation techniques and bioanalysis. The two major approaches use either “evolution in the test tube” of nucleotides for the preparation of aptamers or total chemical synthesis for molecularly imprinted polymers (MIPs). The reproducible production of aptamers is a clear advantage, whilst the preparation of MIPs typically leads to a population of polymers with different binding sites. The realization of bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 171 publications
0
47
0
Order By: Relevance
“…[1] In this respect general synthetic processes with broad applicability in terms of targets to be recognized such as molecular imprinting of polymers are especially appealing. [2,3] Molecular imprinting uses the target as a template during polymerization of functional monomers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1] In this respect general synthetic processes with broad applicability in terms of targets to be recognized such as molecular imprinting of polymers are especially appealing. [2,3] Molecular imprinting uses the target as a template during polymerization of functional monomers.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] While the molecular imprinting concept is fairly universal the functional monomers to provide selective recognition are not, i.e., the library of monomers is rather limited and monomers adequate for a certain protein target may not be necessarily optimal for another. [15] While high affinity MIPs were reported for a number of targets [16,17], the selectivity of protein-MIPs is often enhanced by incorporating in the MIPs compounds known to interact with the target, e.g. substrates or inhibitors of an enzyme target [18,19], aptamers [20] and various nanomaterials [16,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemosensors 2017, 5, 11 2 of 16 than 1200 papers on MIPs are published per year [5][6][7][8][9]. Some ten percent of MIP papers describe artificial receptors for proteins [7,[10][11][12][13], including enzymes [13][14][15][16][17][18][19][20][21].…”
Section: Preparation Of Surface Imprinted Mipsmentioning
confidence: 99%
“…Since then, the technique of self-polymerization has been employed in several studies for the imprinting of proteins on various platforms such as magnetic [51,52], gold [53], or silica nanoparticles [54,55], silicon nanowires [56], 4-vinylphenylboronic acid-based monolithic skeletons [57], gold electrodes [58,59], or multi-walled carbon nanotubes [60]. These studies showed that apart from the advantage of controllable thickness, MIPs comprised of polydopamine exhibit good to excellent binding properties, have high hydrophilicity, biocompatibility, as well as pH (3)(4)(5)(6)(7)(8)(9)(10)(11) and longtime stability [61].…”
Section: Electropolymerizationmentioning
confidence: 99%